Total Quality Management as a Strategic Operational Framework for Quality Assurance and Sustenance in Indian Higher Education Institutions: A Conceptual Review (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
For three decades, one recurring event has shaped how quality assurance works in Indian higher education: the periodic external assessment visit, run either by the National Assessment and Accreditation Council (NAAC) or by the National Board of Accreditation (NBA). That structure has done real work — it has made quality a formal institutional obligation, one that colleges and universities cannot simply ignore. What it has not reliably done is turn quality into a continuous operational habit. This paper argues that Total Quality Management (TQM), reframed as a strategic operational framework rather than a periodic compliance exercise, is what allows an institution to bridge that divide. Curriculum design, faculty performance, research output, student support and institutional governance become, on this reading, everyday sites of quality practice rather than evidence assembled hastily before an assessment cycle. The paper draws on TQM's industrial roots in Deming, Juran and Crosby, and on the education-specific scholarship built by Sallis, by Owlia and Aspinwall, and by Sahney, Banwet and Karunes, to synthesise six interlocking components: a transformation-process view of the institution, SERVQUAL-QFD gap analysis, accreditation-aligned criteria mapping, a leadership and process-management stream, the Owlia-Aspinwall quality dimensions, and excellence-model-based approaches. These six pieces are woven together as a single framework and read against India's shifting regulatory landscape, including the proposed Viksit Bharat Shiksha Adhishthan (VBSA) Bill, 2025, on the premise that a TQM system built around institutional operation, rather than around any single named evaluator, stays relevant no matter who ends up doing the evaluating. The paper wraps up by working through what this means for institutional leadership and policy, being upfront about the limits of a purely conceptual treatment, and flagging the empirical groundwork a subsequent primary study still needs to cover.